Cognitive and Rational-Emotive Behavior Therapy with Couples Theory and Practice. - Vernon,Ann; SpringerLINK eBooks - English/International Collection (2012) (New York : Springer, 2012)
Annotation This book examines problems that couples experience through the life cycle, offering interventions based on cognitive and rational emotive behaviour principles and rooted in research, theory and practice.
Scholarly & Professional
Keywords: Electronic books